ARM MUSCLES EXPLOSIVE POWER TO INCREASE DISCUS THROW SKILL - Miskalena Miskalena; James A.P. Tangkudung (Program Pascasarjana Universitas Negeri Jakarta, 2015)
The purpose of the study is to find out the relationship among arm muscles explosive power, body core flexibility, achievement motivation and discus throw skill. In this case, the samples totaled 50 students from study program of physical education, faculty of pedagogy and science education